2006
DOI: 10.1002/elsc.200520127
|View full text |Cite
|
Sign up to set email alerts
|

Scaling Methods of Sediment Bioremediation Processes and Applications

Abstract: Bioremediation has been argued to be one of the most cost-effective remediation technologies available to reduce soil, sediment, or groundwater contamination, particularly because this approach may allow for the implementation of in-place strategies. Recent trends have advocated the application of innovative sediment stabilization strategies through placement of (reactive) capping material to allow long-term biodegradation of contaminants in these complex biogeochemical environments. The potential long-term ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Consequently, microbial reductive dechlorination increasingly attracted attention due to its activity against highly chlorinated congeners that were not attacked by aromatic hydrocarbon dioxygenases, and it is possibly the first step in transformation of polychlorinated pollutants in the environment. Many studies have demonstrated microbial reductive dechlorination of dioxins from contaminated sediments, sludge and soils [Adriaens and Grbić-Galić, 1994;Adriaens et al, 1995Adriaens et al, , 2006Ahn et al, 2005;Ballerstedt et al, 1997;2004;Barkovskii and Adriaens, 1996;Beurskens et al, 1995;Bunge et al, 2001;Hiraishi et al, 2001;Kao et al, 2001;Vargas et al, 2001;Yoshida et al, 2005].…”
Section: Reductive Dehalogenation Of Dioxinsmentioning
confidence: 99%
“…Consequently, microbial reductive dechlorination increasingly attracted attention due to its activity against highly chlorinated congeners that were not attacked by aromatic hydrocarbon dioxygenases, and it is possibly the first step in transformation of polychlorinated pollutants in the environment. Many studies have demonstrated microbial reductive dechlorination of dioxins from contaminated sediments, sludge and soils [Adriaens and Grbić-Galić, 1994;Adriaens et al, 1995Adriaens et al, , 2006Ahn et al, 2005;Ballerstedt et al, 1997;2004;Barkovskii and Adriaens, 1996;Beurskens et al, 1995;Bunge et al, 2001;Hiraishi et al, 2001;Kao et al, 2001;Vargas et al, 2001;Yoshida et al, 2005].…”
Section: Reductive Dehalogenation Of Dioxinsmentioning
confidence: 99%